Xanthogranulomatous Pyelonephritis of a Lower Pole Moiety in a Duplicated Collecting System Kidney - Jean Paul Wuilleumier; Ariel Schulman; Antonio Montgomery; Ervin Teper (Case Reports in Urology)
Xanthogranulomatous pyelonephritis (XGP) is a destructive inflammatory process which is frequently caused by recurrent urinary tract infections or chronic obstruction by kidney stones. We present a 56-year-old female with an extensive retroperitoneal urinoma and xanthogranulomatous pyelonephritis of the lower pole moiety in a kidney with a duplicated collecting system due to obstructive nephrolithiasis. After drainage of the urinoma, the patient underwent a definitive lower pole heminephrectomy with preservation of the functional upper pole. We review important clinical features of xanthogranulomatous pyelonephritis and considerations for surgery on a duplicated kidney.